Expressions of E2 and E7-HPV16 proteins in pre-malignant and malignant lesions of the uterine cervix. (17th November 2015) - Ramirez, N; Guerra, F; Camporeale, G; Quintana, S; Diaz, LB; Cuneo, N; Villacorta Hidalgo, J; Tatti, SA; Alonso, LG; Borkosky, SS; Prat Gay, G; Palaoro, L
Abstract : Continuous production of the E7 protein from different types of high risk human papilloma virus (HPV) is required for progression of malignancy. We developed antibodies against HPV type 16 E7 and E2 proteins to evaluate their utility as markers for diagnosis during early stages of cervical cancer. Forty biopsies from uterine cervices were diagnosed as low grade intraepithelial lesion (LSIL), high grade intraepithelial lesion (HSIL), squamous carcinoma (SC), in situ adenocarcinoma (ISA) and invasive adenocarcinoma (AC), all of which were infected with HPV 16. Immunohistochemistry was used to investigate the expressions of E7 and E2 (both from HPV 16) and p16. P16 was expressed in eight of 12 LSILs, in all HSILs, in 16 of 18 SC and in all ACs. E2 was expressed in six of 12 LSILs. E7 was positive in eight of 12 LSILs and in all HSIL and carcinomas. The expressions of E2 and E7 of HPV16 related to p16 expression confirmed the value of the viral oncogenic proteins as complementary to histology and support the carcinogenic model of the uterine cervix, because HPVDNA integration into cellular DNA implies the destruction of the gene encoding E2, which suppresses the expression of the E6 and E7 oncoproteins. E2 from HPV16 could be marker for LSILs, while E7 could be a marker for progression of LSILs to HSILs in patients infected by HPV16, because viral typing has little positive predictive value.